Chaotropic and Kosmotropic Anions Regulate the Outcome of Enzyme-Mediated Dynamic Combinatorial Libraries of Cyclodextrins in Two Different Ways - Erichsen, Andreas; Larsen, Dennis; Beeren, Sophie R. (Frontiers in Chemistry, 2021)
We demonstrate how different anions from across the Hofmeister series can influence the behavior of enzyme-mediated dynamic combinatorial libraries of cyclodextrins (CDs). Using cyclodextrin glucanotransferase to catalyze reversible transglycosylation, dynamic mixtures of interconverting cyclodextrins can be formed wherein the relative concentrations of α-CD, β-CD and γ-CD is determined by their intrinsic stabilities and any stabilizing influences of added template (guest) molecules. Here, we find that addition of high concentrations of kosmotropic anions can be used to enhance the effects of added hydrophobic templates, while chaotropic anions can themselves act as templates, causing predictable and significant changes in the cyclodextrin composition due to weak, but specific, binding interactions with α-CD.